2017
DOI: 10.1098/rsos.160605
|View full text |Cite|
|
Sign up to set email alerts
|

Deliberation favours social efficiency by making people disregard their relative shares: evidence from USA and India

Abstract: Groups make decisions on both the production and the distribution of resources. These decisions typically involve a tension between increasing the total level of group resources (i.e. social efficiency) and distributing these resources among group members (i.e. individuals' relative shares). This is the case because the redistribution process may destroy part of the resources, thus resulting in socially inefficient allocations. Here we apply a dual-process approach to understand the cognitive underpinnings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 96 publications
5
42
0
2
Order By: Relevance
“…Labeling the equal outcome as fair in the binary dictator game also aligns our FII predictions with recent findings inCapraro et al (2017) who show that equal outcomes are preferred by intuitive decision makers whereas deliberation allows for a variety of motives to affect decisions.…”
supporting
confidence: 88%
“…Labeling the equal outcome as fair in the binary dictator game also aligns our FII predictions with recent findings inCapraro et al (2017) who show that equal outcomes are preferred by intuitive decision makers whereas deliberation allows for a variety of motives to affect decisions.…”
supporting
confidence: 88%
“…However, very little is known about it. In spite of the importance of this type of decision, I am aware of only one study exploring the cognitive basis of the equity-efficiency trade-off (Capraro, Corgnet, Espín & Hernán-González, 2017). This study found that time pressure promotes equity, while time delay favours efficiency.…”
Section: Extending the Dual-process Approach To Other Types Of Decisionsmentioning
confidence: 99%
“…The effect of culture on strategic interaction has been widely explored [1][2][3][4][5][6][7][8]. However, the effect of culture on focal point selection in tacit coordination games has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%